2013
DOI: 10.1016/j.virol.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV designer T cells progressively eradicate a latently infected cell line by sequentially inducing HIV reactivation then killing the newly gp120-positive cells

Abstract: The current antiretroviral therapy (ART) can effectively reduce plasma HIV loads to undetectable levels, but cannot eliminate latently infected resting memory CD4 T cells that persist for the lifetime of infected patients. Therefore, designing new therapeutic approaches to eliminate these latently infected cells or the cells that produce HIV upon reactivation from latency is a priority in the ART era in order to progress to a cure of HIV. Here, we show that “designer” T cells expressing chimeric antigen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 59 publications
(66 reference statements)
2
46
0
Order By: Relevance
“…We found that the newly designed CAR-T cells, here referred to as VC-CAR-T cells, were able to induce T cell-mediated cytolysis after coculture with gp120-expressing cells and wild-type HIV-1-infected CD4 ϩ T cells. We also found that VC-CAR-T cells display superior potency compared to the CD4-CAR described previously (26,27,(31)(32)(33)(34)(35)(36). Importantly, we have also confirmed that they can effectively kill the reactivated HIV-1-infected CD4 ϩ T lymphocytes isolated from HIV-1-infected patients.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…We found that the newly designed CAR-T cells, here referred to as VC-CAR-T cells, were able to induce T cell-mediated cytolysis after coculture with gp120-expressing cells and wild-type HIV-1-infected CD4 ϩ T cells. We also found that VC-CAR-T cells display superior potency compared to the CD4-CAR described previously (26,27,(31)(32)(33)(34)(35)(36). Importantly, we have also confirmed that they can effectively kill the reactivated HIV-1-infected CD4 ϩ T lymphocytes isolated from HIV-1-infected patients.…”
supporting
confidence: 84%
“…Therefore, we chose to use VRC01-28BBZ-3-expressing T cells, here referred to as VC-CAR-T cells, for subsequent experiments. Previous studies have reported that CD4-based CAR-T cells, referred to here as CD4-CAR-T cells, display direct cytotoxic activity against HIV-1 Env-expressing target cells (26,27,(31)(32)(33)(34)(35)(36). To compare the efficiency of CD4-CAR and VC-CAR, we generated the former by replacing the VC-CAR scFv with the human CD4 extracellular domain and transduced this construct into CD8 ϩ T lymphocytes (Fig.…”
Section: Selection Of the Most Efficient Car Moiety To Identify The mentioning
confidence: 99%
See 2 more Smart Citations
“…The kick-and-kill paradigm gained traction when it was demonstrated that latency reversal (kick) alone, with the LRA vorinostat, was insufficient to cause the death of infected cells in a postactivation in vitro latency model, whereas the addition of expanded HIV-specific CD8 + T cells resulted in infected cell elimination (5). Others have since reported similar results using additional in vitro latency models, combined with natural or engineered CD8 + T cells, or NK cells as effectors (9)(10)(11)(12)(13)(14). These results have motivated the translation of the kick-and-kill approach into clinical trials that, thus far, have failed to achieve reductions in infectious viral reservoirs (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%